BIBLIOMETRIC ANALYSIS OF ACADEMIC PUBLICATIONS ABOUT GREEN SUPPLY CHAIN MANAGEMENT: : Limits and Possibilities - Prado, Nágela Bianca do; Moraes, Gustavo Hermínio Salati Marcondes de (Revista Eletrônica de Gestão e Tecnologias Ambientais, 2022)
This study aims to present a bibliometric overview about the relationship between GSCM and environmental sustainability in academic articles indexed on Web of Science and Scopus databases, between 2000 and 2020. For this, it was used the bibliometric analysis procedure combining a quantitative and a qualitative approach, reporting the main findings through bibliometric indicators and VOSviewer software. In relation to the findings, it was possible to confirm and identify that (a) in the last twenty years the theme has gained relevance, with an increasing number of studies; (b) the main research authors on the topic are American and Chinese, with a special focus on Joseph Sarkis and Syed Khan; (c) the main countries whose universities focus their research on GCSV and sustainability are the United States and China; (d) the Journal of Cleaner Production is the journal that most indexes subjects related to the theme; (e) the manufacturing sector is the most investigated; (f) the effectiveness of implementing GCSV faces numerous barriers, which become more complex according to the region; and (g) recent research is studying the relationship between GSCM and information technology. Finally, the originality of the study lies in providing a broad and in-depth overview about the GSCM framework, combining a mixed analysis methodology, contributing to future research on the theme.